2018
DOI: 10.1371/journal.pone.0193597
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome bisulfite sequencing reveals unique adaptations to high-altitude environments in Tibetan chickens

Abstract: BackgroundTibetan chickens living at high altitudes show specific adaptations to high-altitude conditions, but the epigenetic modifications associated with these adaptations have not been characterized.ResultsWe investigated the genome-wide DNA methylation patterns in Tibetan chicken blood by using whole genome bisulfite sequencing. Generally, Tibetan chickens exhibited analogous methylation patterns to that of lowland chickens. A total of 3.92% of genomic cytosines were methylcytosines and 51.22% of cytosines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
(43 reference statements)
3
8
0
1
Order By: Relevance
“…Approximately 4.3% of cytosine sites were methylated, which is lower than the cortical bones in mice from 6.06 to 6.48% ( Wei et al, 2020 ). The highest proportion of CG methylation in this study was similar to that found in other species ( Wei et al, 2020 ) and tissues ( Li C. W. et al, 2015 ; Li J. X. et al, 2015 ; Zhang et al, 2018 ; Tan et al, 2020 ). Among the gene functional regions, TSSs presented the lowest methylation levels, which was consistent with the results in chickens’ liver ( Tan et al, 2020 ) and blood ( Zhang et al, 2018 ), but inconsistent in cortical bones of mice ( Wei et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…Approximately 4.3% of cytosine sites were methylated, which is lower than the cortical bones in mice from 6.06 to 6.48% ( Wei et al, 2020 ). The highest proportion of CG methylation in this study was similar to that found in other species ( Wei et al, 2020 ) and tissues ( Li C. W. et al, 2015 ; Li J. X. et al, 2015 ; Zhang et al, 2018 ; Tan et al, 2020 ). Among the gene functional regions, TSSs presented the lowest methylation levels, which was consistent with the results in chickens’ liver ( Tan et al, 2020 ) and blood ( Zhang et al, 2018 ), but inconsistent in cortical bones of mice ( Wei et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…Thus the low methylation observed in our data may be specific to the species, tissue, or stage of development. To date, whole-genome bisulfite sequencing studies in G. gallus and other avian species have reported global CpG methylation rates between 50 and 65% (Li et al, 2015;Derks et al, 2016;Lee et al, 2017;Zhang et al, 2017Zhang et al, , 2018, which is lower than the 60-80% that has been reported in mammalian studies. It is possible that the low levels of CpG methylation detected in our data can be attributed to lower CpG methylation rates in avian genomes.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, numerous epigenome-wide association studies (EWAS) have been performed in humans and mice to identify loci at which methylation level is significantly associated with complex and disease traits (Orozco et al, 2015;reviewed in Flanagan, 2015). Bisulfite-sequencing approaches allow for genome-wide assessment of DNA methylation patterns, yet this approach has been underutilized in the chicken thus far (Li et al, 2015;Lee et al, 2017;Zhang et al, 2017Zhang et al, , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, identifying local adaptations as indicated by outlier allele frequencies suggestive of genes under diversifying selection, or by correlations between allele frequency and environmental factors, will require larger sample sizes (at least 8-12 samples per site; Landguth & Schwartz 2014, Pastenes et al 2017, Zhen et al 2017, Homola et al 2019. On the other hand, local adaptation indicated by differences in patterns of gene expression or genomic methylation profiles might require fewer samples (three or fewer depending on the method of comparative analysis; Zhang et al 2018, Xin et al 2019.…”
Section: Discussionmentioning
confidence: 99%